2017
DOI: 10.1038/s41598-017-00898-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytological and molecular characterization of carotenoid accumulation in normal and high-lycopene mutant oranges

Abstract: Ripe Cara Cara sweet orange contains 25 times as much carotenoids in flesh as Newhall sweet orange, due to high accumulation of carotenes, mainly phytoene, lycopene and phytofluene. Only yellow globular chromoplasts were observed in Newhall flesh. Distinct yellow globular and red elongated crystalline chromoplasts were found in Cara Cara but only one type of chromoplast was present in each cell. The red crystalline chromoplasts contained lycopene as a dominant carotenoid and were associated with characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 61 publications
11
33
0
Order By: Relevance
“…The finding that major genes involved in chromoplast biogenesis, starch biosynthesis, and rate-limiting genes for carotenoid biosynthesis were located within the two QTL regions, indicated that activity surrounding chromoplast biogenesis determines the level of carotenoids accumulated and displacement of starch. Our results agree with the findings of Lu et al (2017) in sweet orange, showing that crystalline chromoplast development explained most of the accumulated carotenoids more than the actual carotenoid metabolic pathways genes. The IbOr gene (Goo et al 2015) which is located within our QTL on LG12 interacts with PSY gene on LG3 to enhance chromoplast biogenesis and carotenoid accumulation (Lu et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…The finding that major genes involved in chromoplast biogenesis, starch biosynthesis, and rate-limiting genes for carotenoid biosynthesis were located within the two QTL regions, indicated that activity surrounding chromoplast biogenesis determines the level of carotenoids accumulated and displacement of starch. Our results agree with the findings of Lu et al (2017) in sweet orange, showing that crystalline chromoplast development explained most of the accumulated carotenoids more than the actual carotenoid metabolic pathways genes. The IbOr gene (Goo et al 2015) which is located within our QTL on LG12 interacts with PSY gene on LG3 to enhance chromoplast biogenesis and carotenoid accumulation (Lu et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…For example, silencing of phytoene desaturase ( PDS ) and non‐intrinsic ABC protein 7 ( lNAP7 ) genes leads to Chl degradation and decreased lycopene synthesis in mature tomatoes, due to photobleaching and chloroplast destruction (Fu et al ., ). In citrus, manipulation of the pigment content of chromoplasts affects the structure of the chromoplasts (Lu et al ., ). The number and size of plastids in tomato fruit are attributed to the levels of Chl and lycopene (Cookson et al ., ; Galpaz et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, the mechanism of red-fleshed pigmentation due to carotenoids has attracted increasing amounts of research attention, and relevant candidate genes have been verified in papaya [ 2 ], carrot [ 9 ] and tomato [ 10 ]. Recently, the composition and content of carotenoids in red-fleshed citrus were reported to largely differ from those in pale-fleshed/orange-fleshed citrus [ 11 , 12 , 13 ]. However, owing to the lack of records concerning the breeding history of some red-fleshed citrus cultivars, the naturally occurring highly hybridized genetic background and the long juvenile phase of citrus seedlings [ 14 ], the mechanism of carotenogenesis in red-fleshed citrus remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%